1.56 Synergism between GM-CSF and IL-17 causes enhanced joint pathology via the production of IL-6 and IL-23. (31st January 2014) - van Nieuwenhuijze, Annemarie E M; van de Loo, Fons A; Walgreen, Birgitte; Bennink, Miranda; Helsen, Monique M A; van den Bersselaar, Liduine; Wicks, Ian P; van den Berg, Wim B; Koenders, Marije I
Abstract : Background and Objective: T helper-17 (Th17) cells are important mediators of inflammatory diseases, and are the main pathogenic cell type in many animal models of autoimmunity. Recent studies highlight a surprising role for T-cell derived granulocyte-macrophage colony stimulating factor (GM-CSF) in the pathogenicity of Th17 cells. We examined the mechanism by which interleukin 17 (IL-17) and GM-CSF contribute to cartilage- and bone damage of synovial joints during experimental arthritis, and provide a rationale for combination therapy in auto-inflammatory conditions. Materials and Methods: Collagen-induced arthritis (CIA) was elicited in DBA/1J mice. Neutralizing antibodies to IL-17 and/or GM-CSF were administered after onset of disease for 14 days. Arthritis progression was followed by macroscopic scoring of the paws (maximum score of 12 per mouse). In addition, the effect of local over-expression of IL-17 and/or GM-CSF was studied by adenoviral transfection in naïve knee joints. Results: Combined therapeutic treatment of mice early after the onset of CIA ameliorated disease progression. Macroscopic joint inflammation was significantly reduced, from a total score of 5.6 ± 0.4 for mice treated with isotype control antibodies to 2 ± 0.6 for mice treated with combination therapy. Treatment with anti-IL-17 or anti-GM-CSF alone resulted in scores of 3.4 ± 0.5 and 3.5 ± 0.4, respectively. Simultaneous blocking of GM-CSF and IL-17 was also the most effective treatment in the prevention of radiological bone damage and histological cartilage destruction. To provide further insight in local additive or synergistic effects of IL-17 and GM-CSF, overexpression of IL-17, GM-CSF or the combination was achieved with adenoviral vectors. Inflammatory infiltrate and cartilage- and bone damage developed in all groups from day 1 after adenoviral transfer, with the most severe effect observed in the combination group. On day 7, partial destruction of joint architecture was apparent in knee joints after combined overexpression of IL-17 and GM-CSF. Overexpression of GM-CSF alone induced IL-1β, which production was elevated by IL-17. Interestingly, overexpression of IL-17 alone caused a clear increase in synovial IL-6 production (179 ± 63pg/ml), which was dramatically enhanced in the co-presence of GM-CSF (1.9 ± 0.4 ng/ml). In addition, a strong synergistic effect of combined overexpression was seen on the Th17 differentiation factor IL-23. Conclusions: We show that IL-17 and GM-CSF cause joint damage through synergistic effects on inflammatory mediators in synovial joints. In view of the moderate success of therapeutic IL-17 or GM-CSF blockade in rheumatoid arthritis, combined inhibition of IL-17 and GM-CSF might be an interesting option for patients that do not fully respond to inhibition of the separate cytokines.